Gestão em bibliotecas universitárias públicas: um enfoque tecnológico - França, Maira Nani (2015)
Over the past years there have been several reflections related to rapid changes in the scientific, technological, political, educational and social areas, resulting from technological innovations. More than significant changes in the universities preconized by Cunha, in 2000, it has been experienced in this second decade of the millennium with greater intensity and speed, the reflections of conceptual and structural changes related to education, facing the new settings of the universities - and their libraries, particularly due to governmental policies of restructuring and expansion of the universities. This dissertation seeks to study, analyze and systematize the main ideas that guide and shape the management of public university libraries, specifically with regard to technological innovations. The specific objectives of this research are: contextualize public university libraries in the context of the information society and universities in the country; review the administrative practices adopted by federal public university libraries related to the adoption of TIC in their functional activities; systematize the main ideas that shape the libraries in this logic of planning and implementation of technologies; present an overview of TIC in this segment from a comparative study between the libraries system of the Federal University of Uberlândia (SISBI / UFU) and the Federal University of Santa Catarina (SiBi / UFSC); make a historical record (2009-2014) of TIC and their functionalities, implemented in these libraries and identify the challenges and opportunities to build the university library for the next years. In order to check the differences and similarities between two similar objects that differ in some aspects was adopted in this study the comparative method. This work was elaborated from four constructs / search categories, based on the theoretical basis on the management of university libraries, aiming its review, extracted from the instrument for planning and management proposed by Lubisco (2011), the issues that would likely have major impacts in the university libraries in 2010, besides the main challenges faced by these informational units (Cunha, 2000, 2010), namely: planning and evaluation; staff; users; products and services. From the results obtained was identified the evolution and adaptation of university libraries regarding the use of TIC in order to better meet the information needs of its members. Plan informational unit, view the future, set the path to achieve the proposed objectives are possibilities derived from knowledge management, which can instrumentalize managers to position the libraries in the administrative context of universities, considering their relevance and the value of their services, and not only follow the technological innovations, but having priority in the allocation of budgetary resources and to consolidate up effectively as co- responsible for the generation of process knowledge at the university.